Essential Oil Composition of Stachys antalyensis Y. Ayasligil and P.H. Davis Described Endemic Species from Turkey - FAKIR*, HÜSEYIN; YASAR†, SAMIM; ERBAS, SERHAT (Asian Journal of Chemistry, 2009)
The essential oil obtained from the aerial parts of Turkish endemic Stachys antalyensis Y.Ayasligil and P.H. Davis (Lamiaceae) has been studied. Plant material of S. antalyensis was collected from the locality: C3 Çandir (Isparta), Yazili Canyon Nature Park in Turkey. Aerial parts of plants were dried in shadow than the leaves and flowers were separated from the stems. The essential oil was extracted from the leaves and flowers by hydro distillation method. The average content of essential oil was obtained as 0.2 %. The water-distilled essential oil from dried leaves and flowers of this species was analyzed by GC-MS. A total of 19 components, representing 94.5 % of the oil, were characterized. The major component of essential oil was bicyclogermacrene as 29.4 %. The other important compounds were identified such as β-caryophyllene, spathulenol, β-pinene, viridiferol and elemol.